2003
DOI: 10.1016/s0924-9338(03)00034-8
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and services of psychiatric care in Saxony-Anhalt: assessment with the European Services Mapping Schedule

Abstract: This article describes and analyses the availability of outpatient, inpatient and community-based psychiatric care in Saxony-Anhalt, one of the federal states in the eastern part of Germany. The European Services Mapping Schedule was used to classify 365 institutions. Outpatient care was provided by an average of four private practice psychiatrists per 100,000 inhabitants, which is low when compared to the German average. Ten secure beds (forensic), 48 acute beds, 13 elective beds and 13 day hospital places pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…In the EPSILON study [7], the number of non-hospital residential beds was 3.5 per 100,000 population in Santander, Spain and 36 per 100,000 in Verona Italy. A subsequent study in the Sachsen-Anhalt region of Germany, using an identical methodology, reported over 200 non-hospital residential beds per 100,000 population [8]. It may be that patients living in such structures may have easier access to hospitalisation, or more need for hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the EPSILON study [7], the number of non-hospital residential beds was 3.5 per 100,000 population in Santander, Spain and 36 per 100,000 in Verona Italy. A subsequent study in the Sachsen-Anhalt region of Germany, using an identical methodology, reported over 200 non-hospital residential beds per 100,000 population [8]. It may be that patients living in such structures may have easier access to hospitalisation, or more need for hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in Germany, the number of psychiatric beds remains relatively high and has similar capacity to community residential care such as sheltered housing [32]. The extent of provision of sheltered or staffed accommodation also varies between countries, for instance being more developed in Germany [8] than in Spain [7] or Greece [29]. In the EPSILON study [7], the number of non-hospital residential beds was 3.5 per 100,000 population in Santander, Spain and 36 per 100,000 in Verona Italy.…”
Section: Discussionmentioning
confidence: 99%
“…Integration is considered to be the focus of service system research [ 22 ]. However, a recent systematic review on coverage of MHS found only seven studies, but suggested that coverage data could help optimize the limited resources and the balancing of local and centralized services, despite the scarcity of studies [ 46 ]. This reinforces our starting point of the need for more research into the associations between MHS properties and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies described output planning units including: cost per housing type; beds per 100,000 population; and full time equivalent staff per resident. Service funding, provision and governance were difficult to discern, but public funding plus a mix of direct public and/or NGO service provision were mentioned in 15 studies (15,(18)(19)(20)(21)(22)(23)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Twelve studies described evidence for service efficacy.…”
Section: Scope Of Classification Systemsmentioning
confidence: 99%
“…These are outlined in Table 2 and summarized below. (8,18,19,21,(26)(27)(28)(29)32,33,35,37). These classification systems most commonly used three elements to delineate categories of supported accommodation: size and number of rooms of the physical structures; characteristics of the staff including their qualifications and presence on or off site; and service intensity.…”
Section: Common Features Of Existing Classification Systemsmentioning
confidence: 99%